2012
DOI: 10.5588/ijtld.11.0476
|View full text |Cite
|
Sign up to set email alerts
|

Delays in the diagnosis of pulmonary tuberculosis in Coahuila, Mexico

Abstract: In Coahuila, lack of formal education, living ≥5 km from a health unit, first consultation with a private physician, and being aged ≥46 years contributed to delays in PTB diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…[26] This decrease in patients presenting to a public health facility first in our study could be due to lack of awareness among the community about the availability of free and effective TB treatment services under the RNTCP. The median health system delay was 17 days, similar to those reported in Mwanza (15 days) [27] , Nepal (18 days) [20] and Mexico (18.5 days) [25] lower than that observed in Tanzania (28 days) [2] , Norway (33 days) [3] , Bangladesh (56 days) [22] and Iran (75 Days) [18] . This suggests that the health system delay was not the main problem in the area studied.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…[26] This decrease in patients presenting to a public health facility first in our study could be due to lack of awareness among the community about the availability of free and effective TB treatment services under the RNTCP. The median health system delay was 17 days, similar to those reported in Mwanza (15 days) [27] , Nepal (18 days) [20] and Mexico (18.5 days) [25] lower than that observed in Tanzania (28 days) [2] , Norway (33 days) [3] , Bangladesh (56 days) [22] and Iran (75 Days) [18] . This suggests that the health system delay was not the main problem in the area studied.…”
Section: Discussionsupporting
confidence: 69%
“…[24] In this study, the patient delay was the most important reason for total delay, a finding similar from a study in Mexico. [25] Our findings showed that a private clinic was the first point of contact for 68% of patients and a public health facility for 32% of patients, compared to respectively 43% and 47% in study from the southern part of India. [26] This decrease in patients presenting to a public health facility first in our study could be due to lack of awareness among the community about the availability of free and effective TB treatment services under the RNTCP.…”
Section: Discussionmentioning
confidence: 71%
“…Similar analyses in other settings have revealed treatment delays by private providers and have proposed that these may be due to “deficiencies” [3], poorer knowledge regarding TB management [7, 8] or a lack of “effective diagnostic tools and follow-up routines” [2]. Although these factors may well be contributing, most previous studies did not consider important covariables, such as sputum smear status, which have previously been associated with health system delays [28] and that we found to be an important confounder in analyses of treatment commencement.…”
Section: Discussionmentioning
confidence: 82%
“…However, reports from a variety of contexts have suggested differences in the timely diagnosis and initiation of therapy between public and private sectors [2]. Longer delays have been identified in the private sector, including treatment delays (variably defined as the time from symptom onset to either smear test result, diagnosis or treatment commencement) [36] and health system delays (time from healthcare presentation to treatment initiation) [79]. Surveys of private providers have revealed TB patient management practices that fall short of recommended guidelines in various settings [1016].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Mexico, Nicaragua, and Peru have shown that substantial proportions of people with TB initially seek care in private sector facilities. [13][14][15] A study from Brazil found that a relatively small, albeit growing, percentage of TB diagnostic tests were performed in the private sector. 16 However, among the 78 studies included in a systematic review of public-private partnership models for TB, 12 only one originated from Latin America, and it focused on the involvement of private pharmacies rather than private health facilities.…”
Section: Introductionmentioning
confidence: 99%